Super‐absorbent resin preparation utilizing spent mushroom substrates. Issue 2 (17th April 2013) - Ding, Rui; Gong, Kai
ABSTRACT To find high value‐added utilization for spent mushroom substrates (SMS), a series super‐absorbent sample were prepared with SMS mass ratio between 0% and 100% based on acrylic acid plus SMS, heated with microwave. The maximum absorbency of the composite with 25% SMS ratio in water and saline corresponding to 0.3 wt % initiator is 458 and 61 g/g, respectively; the gel strength of the composite with 25% SMS is two times as high as that of the noncomposited polyacrylate. On SEM pictures, as SMS mass ratio increases the composites resin continuity was interrupted by SMS particles meanwhile some SMS particles are bare; micro‐particles of SMS uniformly dispersed in the acrylic resin forming submicroscopically homogeneous composites. IR spectra show that the composite has different chemical groups and structures from the mechanical mixture. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1098‐1103, 2013